2016
DOI: 10.1038/nature18608
|View full text |Cite
|
Sign up to set email alerts
|

Phenological sensitivity to climate across taxa and trophic levels

Abstract: in all months, and mean precipitation increased in most months (Fig. 2a). 68Spatial variability in climatic change (Fig. 2b,c), necessitates local matching of phenological 69 and climatic datasets rather than the use of regionally-averaged climate data (e.g. Central 70England Temperatures) or large-scale climatic indicators (e.g. North Atlantic Oscillation). 71We did not make the restrictive assumption that biological events would be related to annual CSP precip varied less among trophic levels than the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
744
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 772 publications
(811 citation statements)
references
References 37 publications
21
744
4
2
Order By: Relevance
“…Changes in seasonal timing (phenology) are a common response to recent climate changes in many systems (Parmesan, 2006; Thackeray et al., 2016). The fitness consequences of phenological shifts can be heterogeneous and depend on the environmental and community context (Forrest, 2016; Forrest & Miller‐Rushing, 2010; Pau et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in seasonal timing (phenology) are a common response to recent climate changes in many systems (Parmesan, 2006; Thackeray et al., 2016). The fitness consequences of phenological shifts can be heterogeneous and depend on the environmental and community context (Forrest, 2016; Forrest & Miller‐Rushing, 2010; Pau et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For temperate plants, the timing of spring events, such as leafing and flowering, has been especially well recorded by both professional and citizen scientists. Analysis of the resultant longitudinal data sets reveals that spring phenology has advanced in many species over the past few decades, coincident with rising temperatures (Fitter & Fitter, 2002;Amano et al, 2010;Thackeray et al, 2016). Some of the advancement in phenology will be due to microevolutionary change (Franks et al, 2014), but plastic responses to temperature probably dominate (Nicotra et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In deciduous habitats, for example, the timing of leaf emergence determines the availability of food for many herbivorous insect species (Coyle et al., 2010; Feeny, 1970) and, in turn, insectivorous birds (Perrins, 1991; Van Noordwijk et al., 1995). Any disruption to such trophic synchrony, caused by changes in vegetation phenology, could have far‐reaching consequences for community structure and population dynamics (Post et al., 2009; Thackeray et al., 2010, 2016). Recent research has demonstrated that species and populations can differ considerably in their phenological responses to climate change (Roberts et al., 2015; Thackeray et al., 2010), and this can lead to ecological mismatch between trophic levels (Both et al., 2009; Sagarin et al., 1999).…”
Section: Introductionmentioning
confidence: 99%